Effect of Nozzle Diameter and Raster Angle on the Mechanical Properties of 3D Printed Nylon/ Carbon Fibers - Salman, Marwan A.; Daham, Sadoon R.; Shaheen, Wael H. A.; Mohammed, M. N.; Mustafa, F. F.; Abdullah, Oday I.; Al-Zubaidi, S. (Engineering, Technology & Applied Science Research, 2025)
Fused Deposition Modeling (FDM) is classified as the most commonly used 3D printing process due to its low cost, wide range of material selection, and high accuracy. As an additive manufacturing method, FDM selectively deposits a melted plastic material layer by layer to produce a 3D object according to a geometry defined by a CAD model. The 3D printing process parameters, including infill density, printing speed, and printing orientation, have a huge effect on the mechanical properties of the 3D printed parts. Thus, finding the optimum 3D printing parameters is a very significant task that enriches the FDM 3D printing process, resulting in 3D printed parts with augmented mechanical performance. The present study investigates the effects of the FDM injector’s nozzle diameter and printing path direction (raster angle) on the mechanical properties of the nylon/carbon fiber composite 3D printed parts. The two targeted parameters are optimized through experimental tests on the elastic and flexural strength. Their impact on the nylon/carbon fiber composites’ microstructure is also explored deploying Scanning Electron Microscopy (SEM). The findings provide a comprehensive understanding of the mechanical performance of nylon/carbon fiber composite 3D printed parts. In addition, inspecting the internal microstructure of the materials, especially at the interface zone between the nylon and carbon fiber, provides an explanation of the material composites’ failure mechanism under various loads.